Memory Loss induced by Aspartame in Albino Rats: Study on neurobehavioral changes - Suswidiantoro, Vicko; Saputri, Fadlina Chany; Mun'im, Abdul (Universitas Aisyah Pringsewu, 2021)
Objective: Aspartame (ASP) consumption in various food and beverage products has generated a lot of controversy on safety. Many reports, ASP caused deterioration of health condition likes diabetes, psychiatric disorders, memory loss, etc. This study aimed to investigate the optimization duration of ASP to induce memory loss in Sprague Dawley rats. Methods: The ASP was administered 40 mg/kg BW orally for 28 days in rats. Analysis of memory loss by neurobehavioural changes including latency time, length of track, per cent time and frequency target quadrant using Morris Water Maze (MWM) at day 14, 21, 28, and 24 hours after the last treatment. Results: The administration of ASP showed the time-dependent changes for each indicator of neurobehavioural. The results demonstrated during 28 days of induction showed a significant decrease in latency time, length of track, per cent time and frequency target quadrant. Conclusion: From the results, it can be concluded administration of ASP during 28 days induce neurobehavioural changes related to memory loss in rats. Abstrak: Objektif: Penggunaan aspartame (ASP) sebagai pemanis buatan yang banyak terdapat pada makanan, dan minuman menimbulkan berbagai kontroversi dalam hal keamanan. Berbagai data menunjukkan ASP dapat menyebabkan gangguan kesehatan seperti diabetes, gangguan psikiatrik, penurunan fungsi memori, dll. Penelitian ini bertujuan untuk menentukan waktu durasi penggunaan ASP yang dapat menyebabkan gangguan fungsi memori pada tikus Sprague Dawley. Metode:ASP diberikan secara oral pada tikus dengan dosis 40 mg/kg BB selama 28 hari. Analisis terhadap fungsi memori dilakukan dengan adanya perubahan perilaku pada hewan, meliputi waktu latensi, Panjang lintasan, persentase waktu dan frekuensi kuadran menggunakan Morris Water Maze (MWM) setelah 24 jam setelah pemberian pada hari ke 14,21, 28. Hasil: Pemberian ASP menunjukkan adanya perbedaan waktu pada setiap indicator perilaku. Pemberian selama 28 hari menujukkan adanya perbedaan signifikan pada penurunan waktu latensi, Panjang lintasan, persentase waktu dan frekuensi kuadran. Kesimpulan: Berdasarkan hasil, pemberian ASP selama 28 hari dapat menyebabkan adanya perubahan perilaku yang berkaitan dengan fungsi memori pada tikus.